2017
DOI: 10.18632/oncotarget.19371
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-profile-based methods for understanding selection forces in cancer somatic mutations: a comparative analysis

Abstract: Human genes exhibit different effects on fitness in cancer and normal cells. Here, we present an evolutionary approach to measure the selection pressure on human genes, using the well-known ratio of the nonsynonymous to synonymous substitution rate in both cancer genomes (CN/CS) and normal populations (pN/pS). A new mutation-profile-based method that adopts sample-specific mutation rate profiles instead of conventional substitution models was developed. We found that cancer-specific selection pressure is quite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…The global d N / d S value in cancer genomes is higher than that from germline variation in a human population suggesting a relaxation of negative selection in somatic tissues [ 80 ] (Additional file 3 : Figure S13). Among the factors contributing to weaker negative selection could be copy number gains in cancer genomes creating redundancy and therefore allowing for the accumulation of mutations [ 18 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The global d N / d S value in cancer genomes is higher than that from germline variation in a human population suggesting a relaxation of negative selection in somatic tissues [ 80 ] (Additional file 3 : Figure S13). Among the factors contributing to weaker negative selection could be copy number gains in cancer genomes creating redundancy and therefore allowing for the accumulation of mutations [ 18 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Driver mutations, i.e., those initiate and facilitate carcinogenesis, confer a selective advantage on cancer cells (positive selection), leading to CN/CS>1 for the majority of cancer-related genes. Impressively, up to 30% cancer genes revealed the pattern of mutations under weak positive selection, and mutations under strong purifying selection that were ultimately eliminated from the cancer cell population (Zhou et al 2017;Weghorn and Sunyaev 2017). Moreover, our analysis suggests that passenger somatic mutations, those unrelated to the process of carcinogenesis, are likely be selectively neutral, rather than nearly neutral due to reduced effective clonal size (Kandoth et al 2013), because CN/CS<1-H has been shown highly unlikely.…”
Section: Evolution Of Cancer Somatic Mutations: Dominant Positive Selmentioning
confidence: 74%
“…The argument that carcinogenesis is a form of evolution at the level of somatic cells suggests that our understanding of cancer initiation and progression can be benefited by the molecular evolutionary approaches. One well-known example is to estimate the rate ratio of somatic nonsynonymous to synonymous substitutions (CN/CS) of a protein-encoding gene in cancers, but resulted in inconsistent conclusions (Dees et al 2012;Lawrence et al 2013;Reimand and Bader 2013;Schroeder et al 2014;Porta-Pardo et al 2014;Mularoni et al 2016;Martincorena et al 2017;Zhou et al 2017;Weghorn and Sunyaev 2017).…”
Section: Evolution Of Cancer Somatic Mutations: Dominant Positive Selmentioning
confidence: 99%
“…For each gene or the genome-wide genes as a supergene, we have counted the number of synonymous ( s ) and non-synonymous substitutions ( n ) in coding regions, as well as the number of synonymous ( S ) and nonsynonymous sites ( N ) in total. Based on these, we calculated the ratio of non-synonymous and synonymous substitutions ( K a / K s ) using the following equation: where, s for genes without synonymous substitutions was assumed to be 0.5 as suggested by Wang et al (2011) 1,49,50 to avoid calculation errors due to the few numbers of synonymous mutations detected in genes.…”
Section: Methodsmentioning
confidence: 99%